Apical four-chamber longitudinal left ventricular strain in patients with aortic stenosis and preserved left ventricular ejection fraction: analysis related with flow/gradient pattern and association with outcome. (10th August 2017) - Salaun, Erwan; Casalta, Anne-Claire; Donal, Erwan; Bohbot, Yohann; Galli, Elena; Tribouilloy, Christophe; Hubert, Sandrine; Magne, Julien; Mancini, Julien; Renard, Sebastien; Avierinos, Jean-Francois; Maysou, Laurie-Anne; et al.
Abstract: Aims: To evaluate the prognostic value of apical four-chamber (A4-C) longitudinal strain (LS) in patients with aortic stenosis (AS) Methods and results: In a multicentre cohort, 582 patients (74.3 ± 10.9 years) with moderate or severe AS and preserved left ventricular (LV) ejection fraction (≥50%) were included in this retrospective study. Patients with severe AS were classified in four subgroups according to flow and gradient: low flow (LF) was defined as a stroke volume index <35 mL/m 2 compared with normal flow (NF); low-gradient (LG) as a mean gradient <40 mmHg compared with high gradient (HG). The end point was all-cause of mortality. A4-C LS was measured by two-dimensional speckle tracking and was feasible in all patients. The degree of A4-C LV longitudinal dysfunction increased according to the severity and subgroups of severe AS: from the least to the most impaired: moderate AS, NF/HG, NF/LG, LF/HG, and LF/LG AS ( P < 0.001). During a mean follow-up of 2.6 ± 0.2 years, 58(10%) patients died. The 2-year survival was 76.8% in patients with LF/LG vs. 89.3% in patients with other groups. The best threshold of A4-C LS associated with overall mortality was an absolute cut-off value of |13.75%|. According to this cut-off, the 2-year survival was higher both in patients with moderate AS (96.3 vs. 70%, P = 0.02) and those with severe AS (92.9 vs. 80.9%, P = 0.005). However when dichotomized according to flow/gradient patterns, the association was only statistically significant in the subgroup of patients with NF/HG. By multivariable cox regression analysis, A4-C LS <|13.75| remained independently associated with overall mortality (hazard ratio: 1.8; P = 0.045). Conclusion: A4-C LS is independently associated with death in patients with AS and preserved LVEF, however the flow/gradient pattern should also be considered as an important parameter. The management of these patients may use A4-C LS as a new parameter of evaluation of LV function and prognosis.